2003
DOI: 10.1021/ja034176n
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Palladium−Platinum Dendrimer-Encapsulated Catalysts

Abstract: We report the synthesis, characterization, and catalytic activity of bimetallic palladium-platinum dendrimer-encapsulated catalysts (DECs). These materials are prepared by co-complexation of different ratios of palladium and platinum salts to the interior tertiary amines of fourth-generation, hydroxyl-terminated poly(amidoamine) (PAMAM) dendrimers. Chemical reduction of these composites yields stable, fairly monodisperse, water-soluble bimetallic DECs having sizes on the order of 1.9 +/- 0.4 nm. Evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
258
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 320 publications
(263 citation statements)
references
References 10 publications
5
258
0
Order By: Relevance
“…Results of the type described here are enabled by the high degree of monodispersity resulting from the dendrimer templating approach to nanoparticle synthesis. We recently discovered that this same templating approach can be used to control the composition 3,20,21 and structure 21 of metal nanoparticles, and therefore we are presently studying the effect of these variables on catalyst performance.…”
Section: Published On Web 03/17/2006mentioning
confidence: 99%
“…Results of the type described here are enabled by the high degree of monodispersity resulting from the dendrimer templating approach to nanoparticle synthesis. We recently discovered that this same templating approach can be used to control the composition 3,20,21 and structure 21 of metal nanoparticles, and therefore we are presently studying the effect of these variables on catalyst performance.…”
Section: Published On Web 03/17/2006mentioning
confidence: 99%
“…Additionally, the gas-phase catalytic activity for CO oxidation is higher for the bimetallic catalysts than that for the corresponding Pd-only and Au-only monometallics. 2,3 It has previously been shown that 1-3-nm diameter alloy and core-shell bimetallic PdPt, 4,5 PdAu, 6 PdRh, 7 and AuAg 8 nanoparticles can be synthesized within dendrimer templates. 1 The resulting materials are characterized by a high degree of uniformity in size, structure, and elemental composition, and in some cases they have enhanced solution-phase catalytic activities compared to the analogous monometallic materials.…”
mentioning
confidence: 99%
“…10 For example, G4-NH 2 (Pd 27.5 Au 27.5 ) was synthesized as follows: 0.0924 g of a 14.2 wt % solution of G4-NH 2 in MeOH and 20 µL of 0.3 M HCl were added to 1 L of 99% MeOH, followed by 255 µL of a 0.10 M K 2 PdCl 4 solution. The HCl was added to prevent crosslinking of the G4-NH 2 dendrimer by Pd 2+ (Pd 2+ is used to designate PdCl 4 2-and all its hydrolysis products). 19 After being stirred for 10 min, 255 µL of a 0.10 M HAuCl 4 solution was added.…”
mentioning
confidence: 99%
“…In the nanorods, with a cleaner metallic surface available to perform the reaction and a less effective particle protection, the catalytic activity is better. The catalytic activity measured for both types of BSAfunctionalized nanocrystals was greater than the activity reported for dendrimer-encapsulated platinum nanocrystals [TOF = 50 mol H2/(mol Pt 9 h)] (Scott et al 2003). Platinum particles studied in this work remain stable for months.…”
Section: Triangular Face Atomsmentioning
confidence: 54%